Japan's Imbalance of Payments - Nikolas Müller-Plantenberg (Center for Economic Studies and ifo Institute (CESifo), 2003)
During the past three decades, Japan's current account experienced five large swings. The yen appreciated considerably in periods when the current account boomed, and it depreciated whenever Japan's external performance weakened. However, there has always been a certain lag in the adjustment of the exchange rate. This paper tries to explain these empirical regularities. It argues that as a result of the large movements of the current account, the flows of cash between Japan and ist trading partners fluctuated considerably, which in turn influenced the demand for yen relative to other currencies. To the extent that these cash flows were lagging the current account primarily because of the Japanese lending abroad the exchange rate's response to external imbalances occurred with a delay. Based on the estimated maturity structure of Japan's foreign lending, the paper constructs a measure of payment flows across Japanese borders, which is shown to follow the movements of the exchange rate very closely. The empirical findings raise doubts regarding the feasibility of proposals to depreciate the yen in order to help Japan out of its current economic crisis.
Keywords: 330; yen exchange rate; cash flow; current account; foreign lending maturity structure